Between Exclusion and Inclusion in Religious Education - Humeniuk, Monika (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2020)
The models of religious education presented in the article are alternative spaces of socialization to cope with the sacred and the profane. These formulas are situated on a continuum between exclusion and inclusion and necessitate the development of different social skills in children and adolescents and different communication models.
Keywords: religious education; religion; secularism; exclusion; inclusion; adaptive rationality; rationality emancipatory